ASSOCIATION OF CEREBROVASCULAR ACCIDENT WITH POLYCYTHEMIA VERA - Arshad, Saamia; Iqbal, Tahir; Baig, Wajahat Sultan (Journal of Ayub Medical College Abbottabad, 2019)
Polycythemia Vera is a rare myeloproliferative neoplasm usually having ischemic stroke/thrombotic episode as presenting complaint. The patient reported had history of Cerebrovascular accident (CVA) two years back but blood cell counts were normal that time with no Polycythaemia Vera. Keywords: Polycythemia Vera; Cerebrovascular accident; myeloproliferative neoplasm